Cell-Enriched Fat Grafting Improves Graft Retention in a Porcine Model: A Dose-Response Study of Adipose-Derived Stem Cells versus Stromal Vascular Fraction. Issue 3 (September 2019) - Rasmussen, Bo S.; Sørensen, Celine L.; Kurbegovic, Sorel; Ørholt, Mathias; Talman, Maj-Lis M.; Herly, Mikkel; Pipper, Christian B.; Kølle, Stig-Frederik T.; Rangatchew, Filip; Holmgaard, Rikke; Vester-Glowinski, Peter V.; Fischer-Nielsen, Anne; et al.
Abstract : Background: Cell-enrichment of fat grafts has produced encouraging results, but the optimal concentrations and types of added cells are unknown. The authors investigated the effects of enrichment with various concentrations of ex vivo–expanded adipose-derived stem/stromal cells and stromal vascular fraction on graft retention in a porcine model. Methods: Adipose-derived stem/stromal cells were culture-expanded, and six fat grafts (30 ml) were prepared for each minipig ( n = 13). The authors investigated grafts enriched with 2.5 × 10 6 to 20 × 10 6 adipose-derived stem cells/ml and stromal vascular fraction and nonenriched control grafts. Each pig served as its own control. Magnetic resonance imaging was performed immediately after grafting and 120 days postoperatively before the pigs were euthanized, and histologic samples were collected. Results: The authors recorded an enhanced relative graft retention rate of 41 percent in a pool of all cell-enriched grafts compared to the nonenriched control (13.0 percent versus 9.2 percent; p = 0.0045). A comparison of all individual groups showed significantly higher graft retention in the 10 × 10 6 –adipose-derived stem/stromal cells per milliliter group compared with the control group ( p = 0.022). No significant differences were observed between the cell-enriched groups ( p = 0.66). All fat grafts showed a significantly better resemblance to normal fat tissue in the periphery than in the center ( p < 0.009), but no differences in overall graft morphology were observed between groups ( p > 0.17). Conclusions: Cell-enriched fat grafting improved graft retention and was feasible in this porcine model. No significant differences in graft retention were observed among the various adipose-derived stem/stromal cell concentrations or between adipose-derived stem/stromal cell and stromal vascular fraction enrichment. Future studies using this model can help improve understanding of the role of adipose-derived stem/stromal cells in cell-enriched fat grafting. Abstract : Video Discussion by Edoardo Raposio, M.D., is Available for This Article.